PENGARUH RSNI 1726:2018 BERDASARKAN PETA GEMPA INDONESIA 2017 TERHADAP DESAIN BEBAN GEMPA SEISMIK DI KALIMANTAN SELATAN - Eka Purnamasari (Jurnal Teknologi Berkelanjutan, 2018)
Based on the 2017 Indonesia Earthquake Map and ASCE 7-16, the Indonesia Earthquake Regulation Draft 1717: 2018 was drafted. Tarakan Fault, Mangkalihat Fault, and Meratus Fault are the three main fault zones on Kalimantan Island. Faults located around South Kalimantan are meratus faults with NE-SW direction, also known as thrust fault zone. These faults have a length of more than 100 km which can potentially cause an earthquake with a magnitude of 7. As research material, 14 major cities in South Kalimantan with different zones according to the 2017 Indonesian Earthquake Map were selected. Based on RSNI 1726: 2018 there is a determination new Fa and Fv Site Coefficient values, which affect the magnitude of the Design Response Spectrum and Seismic Design Categories. There was a decrease in the ratio of Ss in Tabalong regency and the increase in the value of Ss is greatest in the mountains of Meratus and Tapin regency. In the Short Period Response Spectrum of 0.2 seconds (SDS) in all cities in South Kalimantan there was a decrease in the ratio based on the site class, with the value of the hard land site (SC) class greater than the class of soft land sites (SE). While the opposite of the 1-second Period Response Spectrum (SD1) an increase in the ratio based on the site class, with the value of the soft soil site class (SE) is greater than the class of hard soil site (SC). The structure of the building with risk category IV was found to have the highest seismic design category, namely KDS D at the Hard Land Site (Sc), occurring in the area within the Ss earthquake zone map of 0.3 to 0.4 g; KDS D at the Medium Land Site (SD) occurs in the area within the Ss earthquake zone map of 0.25 to 0.4 g; KDS D on Soft Land Site (SE) occurs in areas that are in the Ss earthquake zone map worth 0.05 to 0.4 g.